Diet and Social Divisions in Protohistoric Greece: Integrating Analyses of stable Isotopes and Mortuary Practices - Panagiotopoulou, E.; van der Plicht, J.; Papathanasiou, A.; Voutsaki, S.; Katakouta, S.; Intzesiloglou, A.; Arachoviti, P. (Journal of Greek Archaeology, 2018)
The Early Iron Age (EIA, 11th – 8th century BC) in Greece is the transitional period following the end of the Mycenaean civilisation. The first half of this period is the so-called Protogeometric period (11th – 10th century BC) during which the mainland communities had to recover from the collapse of the Mycenaean palatial system, a centralised economic system of a stratified society. Social and economic structures were both severely damaged in the 12th century BC, resulting in various changes in technology, material culture and mortuary practices across the entire Aegean in the ensuing periods. These changes also affected the region of Thessaly, located at the northern margin of the Mycenaean world.